The earliest hylobatid from the Late Miocene of China. Issue 171 (October 2022) - Ji, Xueping; Harrison, Terry; Zhang, Yingqi; Wu, Yun; Zhang, Chunxia; Hu, Jinming; Wu, Dongdong; Hou, Yemao; Li, Song; Wang, Guofu; Wang, Zhenzhen
Abstract: Yuanmoupithecus xiaoyuan, a small catarrhine from the Late Miocene of Yunnan in southern China, was initially suggested to be related to Miocene proconsuloids or dendropithecoids from East Africa, but subsequent reports indicated that it might be more closely related to hylobatids. Here, detailed comparisons of the material, including seven newly discovered teeth and a partial lower face of a juvenile individual, provide crucial evidence to help establish its phylogenetic relationships. Yuanmoupithecus exhibits a suite of synapomorphies that support a close phylogenetic relationship with extant hylobatids. Furthermore, based on the retention of several primitive features of the dentition, Yuanmoupithecus can be shown to be the sister taxon of crown hylobatids. The contention that Kapi ramnagarensis from the Middle Miocene of India might represent an earlier species of hylobatid is not supported here. Instead, Kapi is inferred to be a specialized pliopithecoid more closely related to Krishnapithecus krishnaii from the Late Miocene of India. Currently then, Yuanmoupithecus represents the earliest known definitively identified hylobatid and the only member of the clade predating the Pleistocene. It extends the fossil record of hylobatids back to 7–8 Ma and fills a critical gap in the evolutionary history of hominoids that has up until now remained elusive. Even so, molecular estimates of a divergence date of hylobatids from other hominoids at about 17–22 Ma signifies that there is still a substantial gap in the fossil record of more than 10 million years that needs to be filled in order to document the biogeographic origins and early evolution of hylobatids.